2010
DOI: 10.1136/tc.2009.030700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of California's in-school tobacco use prevention education (TUPE) activities using a nested school-longitudinal design, 2003–2004 and 2005–2006

Abstract: BackgroundCurrent legislative language requires the California Department of Public Health, California Tobacco Control Program, to evaluate the effectiveness of the school-based Tobacco Use Prevention Education (TUPE) programme in California every 2 years. The objective of the study was to measure change and to identify the impact of school-based tobacco use prevention education activities on youth smoking prevalence and attitudes over time, spanning two school year surveys (2003–2004 and 2005–2006).MethodsEva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Although student response rates typically exceeded 70%, and school response rates typically exceeded 80%, 39 some bias was introduced by differential nonresponse in both the NYTS and CSTS. With both surveys, samples excluded dropouts, a significant problem for low-income school districts, such as the Los Angeles Unified School District, where the dropout rate is 17%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although student response rates typically exceeded 70%, and school response rates typically exceeded 80%, 39 some bias was introduced by differential nonresponse in both the NYTS and CSTS. With both surveys, samples excluded dropouts, a significant problem for low-income school districts, such as the Los Angeles Unified School District, where the dropout rate is 17%.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling methodology has been reported elsewhere. 39 Data were collected biennially from California students in grades 6 to 12 beginning with school years 2001 to 2002 through 2011 to 2012 (n = 151 074). Three CSTS administrations preceded the 2007 passage of SB 7, and 3 CSTS administrations followed it.…”
Section: Methods Samplementioning
confidence: 99%
“…Though conclusive evidence of long-term effectiveness is still needed, school-based educational messages can reach large numbers of adolescents at the critical time for uptake of smoking 4. Especially in developing countries, the advantage of school-based education is compounding as the enrolment of the official age-group for a given level rapidly increases.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that school-based tobacco prevention programs can be effective in preventing the initiation of tobacco products if the programs are sufficiently intense and well implemented. [ 4 , 11 15 ] Therefore, if the program is well implemented, we would expect students would be less likely to use tobacco products. Our research shows that students at TUPE-funded schools are indeed less likely to use tobacco products than students at non-funded schools.…”
Section: Discussionmentioning
confidence: 99%
“…It found that greater program implementation was associated with a non-significant decrease in tobacco use over time. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%